2022
DOI: 10.3390/brainsci12091184
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden in Movement Disorders and Neurodegenerative Diseases: Editorial

Abstract: Caregiver burden is still an unmet need in the treatment of many neurodegenerative diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In the interviews, participants shared similar physical and mental treatment and di culties, during their work, formal caregivers have to perform some unwanted tasks, such as cleaning private parts and cleaning up urine, stool, or vomit, with no freedom and little dignity, sometimes, they even have to endure criticism from clients. Just as previous literature has reported, formal caregivers experience signi cant physical and psychological strain [16,[18][19][20][21]23]. More than that, in this study we found that in order to compensate for the heavy burden, they were still striving to maintain their internal and external motivations and responsibilities to actively explore a variety of coping strategies.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the interviews, participants shared similar physical and mental treatment and di culties, during their work, formal caregivers have to perform some unwanted tasks, such as cleaning private parts and cleaning up urine, stool, or vomit, with no freedom and little dignity, sometimes, they even have to endure criticism from clients. Just as previous literature has reported, formal caregivers experience signi cant physical and psychological strain [16,[18][19][20][21]23]. More than that, in this study we found that in order to compensate for the heavy burden, they were still striving to maintain their internal and external motivations and responsibilities to actively explore a variety of coping strategies.…”
Section: Discussionsupporting
confidence: 48%
“…Formal caregivers, who are considered "Invisible Patients" [17], suffer from a high physical and psychological burden [18,19]. The uncontrollable and disruptive behavior of the elderly with disabilities, which contributed to the formal caregivers' multifaceted burdens in stressful situations, affected their health and quality of life [16,20,21]. Gao et al [22] systematically reviewed 35 studies with a total of 3,268 caregivers and found that caregivers typically received 2.4 to 3.5 fewer hours of sleep per week than the non-caregiving controls.…”
mentioning
confidence: 99%
“… 14 Studies in neurodegenerative diseases, such as amyotrophic lateral sclerosis, Parkinson, Huntington’s disease or dementia, report an increasing disease severity and an autonomy loss of the patients as relevant factors for an increasing caregiver burden. 15 Although essential findings from these studies may be transferred to the informal care situation of people with FA, evidence concerning the economic burden of FA is still inconclusive, especially from a societal perspective that includes individuals’ and caregivers’ productivity losses next to the utilisation of healthcare services.…”
Section: Background and Rationalementioning
confidence: 99%